Cognitive Beliefs and Future Time Perspectives: Predictors of Mortality and Longevity - Prem S. Fry; Dominique L. Debats (Journal of Aging Research)
On the basis of postulates derived from cognitive-behavioral theory, research and therapy, the authors explored the extent to which older adults' cognitive beliefs of a just world and their perspectives on future time and similarity or self-continuity with the future self are predictors of long-term survival. After baseline assessment of health and cognitive beliefs and future perspectives of time and self-continuity as predictors of mortality, 440 participants (ages 65 to 87) were followed longitudinally for 6.5 years. Consistent with our hypotheses, findings demonstrated that a significantly higher percentage of survivors were individuals who showed higher scores on beliefs in a just world and on both the future time perspective and the future self-continuity perspective at the time of baseline assessments. Conversely, mortality risk was much higher for individuals who scored low on these predictor variables, and high on distrust. Implications for health and longevity are discussed.